Promosi Digital dan Diferensiasi Produk Terhadap Keputsan Pembelian Seblak Panyileukan di Kota Bandung - Mela Ratna Sari; Halimah Zahrah (Indo Publishing, 2026)
This study aims to analyze the influence of digital promotion and product differentiation on purchasing decisions of Seblak Monmon in Panyileukan, Bandung City. The research method uses a quantitative approach with descriptive verification design. The research population consists of Management students from the class of 2022 at Universitas Muhammadiyah Bandung, with a sample determined using the Slovin formula. The sampling technique employed is stratified random sampling. Data collection uses a Likert scale questionnaire, analyzed using multiple linear regression with SPSS. Results indicate that digital promotion has a positive and significant effect on purchasing decisions, product differentiation has a positive and significant effect on purchasing decisions, and simultaneously digital promotion and product differentiation significantly influence purchasing decisions with a strong contribution. This research provides practical implications for culinary MSME actors to optimize digital promotion strategies through social media and enhance product differentiation to increase competitiveness and sales volume